1998
DOI: 10.1063/1.872997
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid magnetohydrodynamic-particle simulation of linear and nonlinear evolution of Alfvén modes in tokamaks

Abstract: Linear and nonlinear properties of moderate-toroidal-number (n) shear-Alfvén modes in tokamaks are investigated by using a hybrid MHD-particle simulation code, which solves the coupled set of MHD ͑magnetohydrodynamic͒ equations for the electromagnetic fields and gyrocenter Vlasov equation for a population of energetic ions. The existence of unstable toroidal Alfvén eigenmodes ͑TAE's͒ and their kinetic counterpart is shown for low values of the energetic-ion pressure gradient. Above a certain threshold value, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(149 citation statements)
references
References 46 publications
6
143
0
Order By: Relevance
“…The code XHMGC, developed at the Frascati laboratories, is the extended version [27] of the HMGC [15,26], a nonlinear code based on the hybrid MHD gyrokinetic model [31].…”
Section: A Xhmgcmentioning
confidence: 99%
See 2 more Smart Citations
“…The code XHMGC, developed at the Frascati laboratories, is the extended version [27] of the HMGC [15,26], a nonlinear code based on the hybrid MHD gyrokinetic model [31].…”
Section: A Xhmgcmentioning
confidence: 99%
“…Both numerical and analytic works [15,16] have shown that these modes saturate because a macroscopic distortion of the whole fast-ion pressure profile, accompanied by a significant variation of mode frequency and spatial structure. It has been shown [16] that this mechanism can give rise to avalanches, with an outwardly moving front of pressure gradient: shear-Alfvén continuum oscillations are driven progressively unstable by the radially drifting free energy source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hybrid MHD-Gyrokinetic Code (HMGC) [27] can calculate the 4D (e.g. (ρ,θ,v perp ,v para )) alpha particle density in the presence of Alfvén modes.…”
Section: Effect Of Mhd On the Heat Loadmentioning
confidence: 99%
“…Strong energetic particle redistributions are predicted to occur above the EPM excitation threshold [46] in 3D Hybrid MHD-Gyrokinetic simulations [47]. Due to the intrinsic EPM resonant character and their locahzation at the radial position where the drive is strongest [48,49,50], EPMs rapidly redistribute energetic particles.…”
Section: A^ = {(0^/(oj){l-(0p/(o)[l+ (L6{ro/r)^^^ + 05^q^'^ mentioning
confidence: 99%